Drug repositioning of antiretroviral ritonavir for combinatorial therapy in glioblastoma. (November 2020) - Rauschenbach, Laurèl; Wieland, Anja; Reinartz, Roman; Kebir, Sied; Till, Andreas; Darkwah Oppong, Marvin; Dobersalske, Celia; Ullrich, Vivien; Ahmad, Ashar; Jabbarli, Ramazan; Pierscianek, Daniela; Fröhlich, Holger; et al.
Abstract: Background: The protease inhibitor ritonavir (RTV) is a clinical-stage inhibitor of the human immunodeficiency virus. In a drug repositioning approach, we here exhibit the additional potential of RTV to augment current treatment of glioblastoma, the most aggressive primary brain tumour of adulthood. Methods: We explored the antitumour activity of RTV and mechanisms of action in a broad spectrum of short-term expanded clinical cell samples from primary and recurrent glioblastoma and in a cohort of conventional cell lines and non-tumour human neural controls in vitro . To validate RTV efficacy in monotherapeutic and in combinatorial settings, we used patient-derived xenograft models in a series of in vivo studies. Results: RTV monotherapy induced a selective antineoplastic response and demonstrated cytostatic and anti-migratory activity at clinical plasma peak levels. Additional exposure to temozolomide or irradiation further enhanced the effects synergistically, fostered by mechanisms of autophagy and increased endoplasmic reticulum stress. In xenograft models, we consequently observed increasing overall survival under the combinatorial effect of RTV and temozolomide. Conclusions: Our data establish RTV as a valuable repositioning candidate for further exploration as an adjunct therapeutic in the clinical care of glioblastoma. Highlights: Ritonavir exhibits selective antitumour activity at clinically relevant drug levels. Ritonavir boosts temozolomide effects in vitro and in vivo. Repositioning of ritonavir as an adjunct therapeutic should be considered.